Disentangling Diagenesis From the Rock Record: An Example From the Permo‐Triassic Wordie Creek Formation, East Greenland - Roberts, J; Turchyn, AV; Wignall, PB; Newton, RJ; Vane, CH (American Geophysical Union, 2018)
The measurement of isotope ratios in sedimentary rocks deposited over geological time can provide key insights to past environmental change over important intervals in the past. However, it is important to be aware that secondary alteration can overprint the original isotopic records. We demonstrate this principle using high-resolution carbon, sulfur, and oxygen isotope measurements in organic carbon, pyrite, and carbonate minerals (δ 13 C org , δ 34 S pyr , δ 34 S CAS , δ 13 C carb , and δ 18 O carb ) and kerogen analyses (HI and OI) from the Wordie Creek Formation, East Greenland. These sediments were initially deposited across the Permo-Triassic transition, but as we will show, the carbonate record has been altered by interaction with meteoric water significantly after initial deposition. Comparison of the better preserved organic carbon and pyrite records with a proximal Permo-Triassic sequence reveals significant pyrite-sulfur isotope variability across the Permo-Triassic transition. This regional heterogeneity argues against basin-wide euxinia and instead suggests localized changes in sulfur fractionation in response to variations in organic carbon flux. This hypothesis can be used to explain seemingly inconsistent regional trends in other sulfur isotopes across the Permo-Triassic transition.